NUEVA ESPECIE Y SUBESPECIE DE CENTRIS (HYMENOPTERA: APOIDEA) ASOCIADAS A PROSOPIS TAMARUGO - Toro, H.; Chiappa, E. (Acta Entomológica Chilena, 2022)
Centris mixta lamarugalts n. subsp. and Centris moldenket n.sp. from ihe salí deserl, in ihe north pan ol Chile, are described. C. mixta lamarugalts, associated wiih trees of the genus Prosupis, is very abundant for a short period and constituie the main animal f<xxl for larger predators.